Determinant service quality factors for green logistics service providers of cross-border trade - Booyarit. P., Pichit, P., Utayartana, N.,; Mustakim, M., Abaidullah, M., (Opción)
The respondents of this research were 384 of logistics service providers located at cross border areas of Malaysia, Laos, Cambodia and Myanmar. Stratified random sampling is used on samples through the structured questionnaires and regression. Finding of this research revealed that by practicing on green and service quality will improve on the logistics performance as well as quality of the overall logistics businesses. It also suggests that the logistics service providers should deliver on the Green Quality at cross-border trade activities. This research is able to support on logistics providers and understand on the importance of green logistics service quality.